"HOMO SOMATICUS": Persoalan Manusia dan Tubuhnya - Gunawan, Leo Agung Srie; Tinambunan, Laurentius (LOGOS, 2024)
Homo somaticus is the primary reality of human beings. Humans are recognized as such through their bodies and interact with both others and the world using their bodies. This article aims to argue for the existential importance of the human body. The article explores the nature and functions of the human body through the lens of phenomenology. Homo somaticus acknowledges that the human body possesses uniqueness among other creatures. As homo somaticus, humans have five fundamental body functions. Firstly, the worldly body signifies that humans are “beings-in-the world,” integrating with the world through their bodies. Secondly, the epistemological body indicates that humans acquire, assimilate, and convey knowledge through their bodies. Thirdly, the economic body suggests that the body becomes a determinant of possession, assuming the existence of a body. Fourthly, the ascetical body highlights the necessity of engaging in human activities to cultivate valuable virtues. Fifthly, the sexual body identifies the experiences shared by men and women, enabling biological reproduction and shaping social relationships. Homo somaticus underscores that the spirit is embodied, with the spirit being manifested through the body in the world. Nevertheless, the body is an integral part of human existence in the world